2019
DOI: 10.3892/ijmm.2019.4242
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑photoaging effect of fermented agricultural by‑products on ultraviolet B‑irradiated hairless mouse skin

Abstract: Processed products from agricultural produce generate a large number of agricultural by-products that contain a number of functional substances. These are often discarded owing to the lack of suitable processing methods. The present study investigated the anti-photoaging properties of fermented rice bran (FRB), soybean cake (FSB) and sesame seed cake (FSC) on ultraviolet B (UVB)-irradiated hairless mouse skin. Results indicated that the oral administration of FRB, FSB and FSC effectively inhibited the UVB irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In previous studies on FLE products, analysis of the structure and content of constituents of FLE mushroom (Xue, Ma, et al., 2020), analysis of the bio‐active capacity of FLE‐derived polysaccharides (Kim, Kim, et al., 2007), food development (Jung et al., 2016; Kim, Kim, et al., 2007), and evaluation of biological activities, including anti‐cancer (Liu et al., 2009; Zhong et al., 2012), anti‐skin photoaging (Choi et al., 2019), and anti‐obesity effects (Kim, Lee, et al, 2017), have been performed. In particular, several studies have recently described the development of LE‐fermented food materials using apple or pear pomace, rice bran (Kim et al., 2019; Lee et al., 2018), and LE‐fermented beverages and foods using black rice ( Oryza sativa Linne) (Park et al., 2012; Zhang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on FLE products, analysis of the structure and content of constituents of FLE mushroom (Xue, Ma, et al., 2020), analysis of the bio‐active capacity of FLE‐derived polysaccharides (Kim, Kim, et al., 2007), food development (Jung et al., 2016; Kim, Kim, et al., 2007), and evaluation of biological activities, including anti‐cancer (Liu et al., 2009; Zhong et al., 2012), anti‐skin photoaging (Choi et al., 2019), and anti‐obesity effects (Kim, Lee, et al, 2017), have been performed. In particular, several studies have recently described the development of LE‐fermented food materials using apple or pear pomace, rice bran (Kim et al., 2019; Lee et al., 2018), and LE‐fermented beverages and foods using black rice ( Oryza sativa Linne) (Park et al., 2012; Zhang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The produced ROS activates downstream key transcription factors such as mitogen-activated protein kinase (MAPK) and nuclear factor-κB (NFκB) and nuclear factor-erythroid 2-related factor-2 (Nrf2) and finally triggers the secretion of pro-inflammatory cytokines including interleukin (IL)-1β and tumor necrosis factor-α (TNF-α) [ 35 ]. In addition, excessive accumulation of ROS increases MMP activity, resulting in destruction of extracellular matrix (ECM) via collagen degradation [ 36 ]. Additionally, it has been reported that topical administration of AME ameliorates pro-inflammatory response via suppression of ROS-MAPK-NF-kB signaling pathway in a mouse model of tetradecanoylphorbol-13-acetate (TPA)-induced ear edema model [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The UVA radiation-mediated photoaging and skin injury have been characterized by decreased elasticity of the skin, wrinkle formation, and heavy damages of the extracellular matrix [30]. Furthermore, skin inflammation and keratin thickening also contribute to the signs of photoaging [31]. Histopathological examination reveals that exposure to short-term UVA light caused photodamages in the mouse skin which was evident by the altered skin architecture.…”
Section: Discussionmentioning
confidence: 99%